The Implementation and Impact of the First 1000 Days of Life Program on Stunting Prevention - Nurdivanuha, Indira; Wibawani, Sri (Journal of Social Studies Arts and Humanities (JSSAH), 2025)
This study aims to evaluate the implementation of the First 1000 Days of Life (HPK) Movement Program as a key strategy for reducing stunting in Sumberasih District, Probolinggo Regency. The program, established under Regent Regulation No. 15 of 2019 concerning the Acceleration of Integrated Stunting Prevention, was assessed using the public policy implementation model proposed by Randall B. Ripley and Grace A. Franklin, which focuses on three dimensions: compliance with regulations, smooth execution of routine functions, and achievement of intended outcomes. The study employed a qualitative descriptive method, with data collected through interviews, observation, and documentation involving local government officials, health center staff, and community health cadres. The findings reveal that, while most policy implementers demonstrate compliance with established procedures, challenges remain in program execution and outcomes. Several activities—such as nutritional supplementation, exclusive breastfeeding, and immunization—faced irregular participation and limited adherence among target groups. Consequently, the program has yet to achieve significant reductions in stunting prevalence in Sumberasih District. Strengthening inter-sectoral coordination, enhancing community engagement, and ensuring adequate resource allocation are essential to improving the program’s effectiveness in achieving sustainable stunting reduction.